A influência do telhado verde no comportamento estrutural das lajes maciças - Souza, Wriel Herison Soares de (Universidade Federal Rural do Semi-Árido, 2020)
The upward population growth that can lead to the accelerated development of urban areas, causes drastic effects on the environment. In this scenario the green cover comes as ecological solution for this, because this type of coverage has much additional benefits, ranging from improving the aesthetics of the building to improve its thermal comfort. In this context, the present work aimed to dimension and analyze the structural behavior of massive slabs when a green roof was implemented through the investigation of the Service Limit State (ELS) and the Ultimate Limit State (ELU). To calculate and dimension the slabs as well as analyze the ELS and ELU, the TQS software in its student version was used and through the data obtained a comparative and analytical process was carried out, divided into four stages of load implementation referring only to the loads of coverage contained in NBR 6118: 2014 (that deals with the design of concrete structures), in addition to loads of extensive, semi-intensive and intensive green cover. In this analysis process, it can be observed that the increase in loads from the green roofs causes considerable impacts on the ELS of the slabs, generating cracks and a considerable percentage increase in the arrows reaching 108.33%. In view of this, the need to study in more detail the structural impact of implementing green cover is valid.
Monografia
Keywords: TQS; Lajes maciças; ELU; ELS; Cobertura verde; TQS; Massive slabs; ELU; ELS; Green coverage; ENGENHARIAS::ENGENHARIA CIVIL